Cloning and Expression Analysis of IGF3 in Turbot (Scophthalmus maximus) - Jiarong ZHANG; Hongyu QIN; Ting XIE; Xiaoyu ZHANG; Feixia LI; Junxian LÜ; Yudong JIA (Progress in Fishery Sciences, 2024)
The insulin-like growth factor (IGF) system plays a key regulatory role in biological processes, such as growth, reproduction, early development, cell differentiation, and proliferation, in fish and other vertebrates. The IGF family system consists of two IGFs (IGF1 and IGF2), two IGF receptors (IGF-1R and IGF-2R), and six IGF-binding proteins (IGF-binding proteins IGFBP1–6) in mammals. By binding to the cell surface-specific receptor (IGF-Rs), IGFs activate the activity of related protein kinases, initiate the signaling cascade in the cell, and participate in the regulation of various biological reaction processes. The research on fish IGFs mainly focuses on IGF1 and IGF2, and several studies have confirmed that they are widely involved in multiple biological processes, such as growth regulation, immune response, gonadal development, and maturation. IGF3 is a fish-specific sub-type; it was first detected in zebrafish (Danio rerio) and Nile tilapia (Oreochromis niloticus) in 2008 and plays an important role in gender differentiation in many reports. However, it is unclear whether it affects ovarian development.Turbot (Scophthalmus maximus) is an economically valuable flatfish species that is widely farmed in Europe and China. It cannot spawn eggs naturally in captivity and needs to be hand-stripped and artificially fertilized. The IGF system plays an important role during turbot ovary maturation. In this study, the full-length turbot IGF3 sequence was obtained via RACE cloning technology, its bioinformatics characteristics were analyzed, and the tertiary structure and docking situation were predicted. The relative expression levels during the whole tissue and ovarian development were detected using qRT-PCR. Hematoxylin-eosin staining was used to determine the gonadal development stage. The results showed that the full-length cDNA sequence of turbot IGF3 was 1 255 bp, encoding 259 amino acids, and displayed the highest homology with halibut (Hippoglossus stenolepis). A total of 33 amino acid signal peptides and 59 amino acid IGF-specific domains were found. It was a hydrophilic protein with a molecular mass of 26.39 kDa and a hydrophobic isoelectric point of 8.13. The turbot IGF3 is highly homologous with other fish. Turbot IGF3 is a hydrophobic protein, and its tertiary structure consists of three α spirals connected in series, closely integrated with IGF-1R and IGF-2R. igf3 is expressed differently between female and male turbot. In the liver, kidney, stomach, gonads, and brain, the male IGF3 expression was significantly higher than in females. In the heart, intestines, and pituitary gland, female IGF3 expression was significantly higher than males; however, the difference was not significant in the spleen. In male turbot, igf3 is mostly expressed in the brain, while in female turbot, igf3 is mostly expressed in the brain and intestine. During the five stages of development of turbot ovaries (previtellogenesis, early vitellogenesis, late vitellogenesis, migratory nucleus, and atresia), igf3 expression increased significantly in late vitellogenesis and maintained high expression in the migratory nucleus stage and decreased in the atresia stage. The results showed that turbot IGF3 has typical IGF family structure characteristics: local endocrine factors, widely distributed in tissues, significant sex dimorphism, and participates in regulating the growth and maturation of oocytes. Therefore, these findings lay a foundation for an in-depth research on the effects of IGF3 on ovarian development and oocyte maturation in turbot and provides crucial ideas for exploring the novel functions of IGF3 in fish.